Students and drug Use: A Study of Personality Characteristics and Extent of Drug Using Behavior - Riggs, D. Elaine (Canadian Journal of Counselling and Psychotherapy, 2012)
This research was designed to determine the existence of differences on selected personality and attitudinal variables, among groups of adolescents, categorized according to the extent of drug usage charac- teristic of their respective memberships. The sample population consisted of 60 subjects, selected from the grade-twelve student body of a large Edmonton composite high school. The subjects comprised three groups of 20 (10 male and 10 female) individuals, categorized as: habitual drug users, occasional drug users, and non drug users. Individuals inclusive of the three groups were matched carefully to control for age, sex, and educational level. Measures employed included the Edwards Personal Preference Sched- ule and A Survey of the Opinions of Youth, a scale developed by the writer for purposes of examining the direction and intensity of attitude toward drug usage. Groups were found to differ significantly on four of the personality variables measured, and on attitude toward drug usage. Implications for further research exploration, education, and preven- tive and therapeutic services were drawn from the findings.